PENGARUH DEBT TO EQUITY RATIO DAN RETURN ON EQUITY RATIO TERHADAP PRICE EARNING RATIO PADA PERUSAHAAN PROPERTY DAN REAL ESTATE DI BURSA EFEK INDONESIA PERIODE TAHUN 2019-2023 - Sahnaz Aulia Ika; Isep Amas Priatna (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of Debt To Equity Ratio and Return On Equity Ratio on Price Earning Ratio in Property and Real Estate sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019-2023, both partially and simultaneously. The method used is a quantitative method. The population in this study were Property and Real Estate sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023. The research sample was 6 Property and Real Estate companies. Data analysis was carried out using panel data analysis techniques. The results of the study showed that Debt to Equity and Return on Equity had an effect on Price Earning Ratio with a hypothesis test of the F-count value of 8.006 with this significance being less than 0.05 (0.001861 <0.05). Debt to Equity Ratio has an effect on Price Earning Ratio with the hypothesis test obtained a t-count value of 3.906378> t-table which is 1.70329 with a significant value of <0.05. Return on Equity Ratio does not affect Price Earning Ratio with the hypothesis test obtained a t-count value of -0.606742 <t-table 1.70329 significant>0.05.